Evolving conceptions of silvopasture among farmers and natural resource professionals in Wisconsin, USA - Mayerfeld, Diane; Keeley, Keefe O.; Rickenbach, Mark; Rissman, Adena; Ventura, Stephen J. (Frontiers in Sustainable Food Systems, 2023)
Silvopasture has gained attention as an agroecological practice that may simultaneously meet farmer goals and provide environmental benefits, including climate change mitigation. At the same time there are significant concerns about the potential for livestock to damage trees and forest soils. Like other innovative agroecological systems, silvopasture combines management complexity with limited research knowledge. Unlike annual crops, the effects of silvopasture management can take decades to assess and require forestry as well as agronomic expertise. We conducted mixed-methods research on silvopasture attitudes and knowledge among farmers, agricultural advisors, and foresters in Wisconsin between 2014 and 2019. We asked: (1) How do farmers who practice grazing, agricultural advisors, and foresters perceive silvopasture? and (2) How did coverage of silvopasture change between 2009 and 2019 in a popular grazing publication? Perceptions of silvopasture were influenced by recent weather history, markets for forest and agricultural products, existing land uses, and other contextual factors. Some farmers and agricultural advisors were committed to silvopasture despite significant obstacles to implementing the practice. Over the course of the study period agricultural advisors increased their willingness to provide silvopasture advice to farmers and professional colleagues, and coverage of silvopasture increased in a popular grazing publication. Finally, a multi-county supportive community of practice was associated with greater enthusiasm for the practice. The greater acceptance of silvopasture among resource professionals follows an increase in silvopasture research and outreach in the region. This interest in silvopasture suggests both a need for, and openness to, greater collaboration among forestry and agricultural professionals and farmers to develop sustainable silvopasture standards.